Shockwave Therapy Versus Dry Needling for the Management of Iliotibial Band Syndrome: A Randomized Clinical Trial: - Maghroori, Razie; Khosrawi, Saied; Karshenas, Leila (Galen Medical Journal, 2021)
Background: Iliotibial band syndrome (ITBS) is a common leading cause of lateral knee pain. Despite varieties of medical and non-medical treatments proposed for the management of ITBS, the best therapeutic approach for its treatment remained a significant question. The current study aims to compare the outcomes of dry needling (DN) versus shockwave therapy (SWT) in the management of ITBS. Materials and Methods: This randomized clinical trial was conducted on 40 patients diagnosed with ITBS. The patients were randomly divided into two treatment groups of DN (n=20) and SWT (n=20). Visual analog scale for the pain assessment, Lower Extremity Functional Scale (LEFS) for the function evaluation, and length of the iliotibial band were assessed at baseline, immediately after the cessation of the intervention, and within four weeks. Results: The two groups were similar regarding demographic characteristics (P>0.05). Both approaches could efficiently lead to improved pain (P<0.001) and promoted function based on LEFS (P<0.001); however, iliotibial band length (ITBL) did not alter remarkably (P>0.05). The groups were similar in terms of pain score, LEFS, and ITBL at all of the assessment intervals (P>0.05), but the pain score within four weeks following the interventions that were significantly better in DN (P=0.023). Conclusion: Based on our results, DN, as well as SWT, could remarkably lead to an improvement in pain and function among patients resenting from ITBS; however, none of the approaches was superior over the other. [GMJ.2021;10:e2174]